Distribuição e interação parasito-hospedeiro de bivalves da água doce no Novo e Velho Mundo - Santos, Rogério Conceição Lima dos (2019)
One of the fundamental components for species protection is to understand their distribution and the adjacent factors that determine their permanence at the sites. For freshwater mussels, understanding their relationship with the environment and their hosts, as well as enabling conservation, helps maintain the important roles that these organisms play in aquatic ecosystems. In this thesis i) investigated the potential distribution of Haasica balzani, an endemic mussel to South America, using ecological niche models and calculating how much of rivers with suitable habitats are inserted in conservation units; ii) I analyzed, based on the theory of metacommunities, if the local conditions of 35 lakes in a floodplain are more determinant for the mussel assemblages, in relation to the dispersal potential of the species;(iii) I described how Castalia ambigua during its reproductive period uses techniques to attract host fish and; (iv) using an experiment and artificial infestation, I analyzed if host fish that co-occur with mussels have local adaptation in relation to parasitism. I found that (i) there are just over 6% of the rivers with favorable environmental conditions for the occurrence of endemic of H. balzani; (ii) substrate characteristics and quantity of organic matter are strong structurers of the abundance and presence and absence of mussels in lakes in a floodplain; (iii) C. ambigua has morphological adaptations for possible attraction of the host fish; and (iv) hosts that have never had contact with mussels have low larval parasitism rejection rates. My findings indicate that protected areas for freshwater mussel should consider the region's watershed as the basis for the boundaries. Moreover, environmental conditions limiting the distribution and parasite-host relationship must be considered in conservation plans.